Coaches: Pedagogues of Sport? Methodological Attempt to Study the Pedagogical Beliefs of Hungarian Football Coaches - Varga Dániel (Sciendo, 2017)
Not only are coaches supposed to be excellent in their sports, but they should also be good pedagogues. However, according to public opinion, most coaches' only aim is to reach the highest performance possible with their athletes. The objective of this paper is to examine whether this common assumption is also true of football coaches. Adapting the concept of a nationwide study of teachers' pedagogical views, the author attempts to discover Hungarian football coaches' pedagogical beliefs, their opinions on the most important tools of education, the content of human values transmitted during education, and their educational creeds. At the same time, the paper analyzes how the conceptual framework and the methods used in the research among the teachers can be transformed to the special conditions regarding the coaches' work. The results of the research show how the football coaches interpret the term "education," what they think about the most influential tools of education, and which educational values and creeds they identify themselves. The conclusion of the paper is that both the findings of a pilot study among football coaches and the adaptation of the methods used in the research to reveal the teachers' pedagogical views proved to be beneficial and instructive.